Carbon pricing: Swift introduction of a climate dividend needed, reduce at higher incomes - Stefan Bach; Mark Hamburg; Simon Meemken; Marlene Merker; Joris Pieper (DIW Weekly Report, 2024)
With the transition from the German national emissions trading system to the European Emissions Trading System (EU ETS2) from 2027, final consumer prices for fossil motor and heating fuels are likely to rise significantly. This increase will affect low-income households more noticeably, as they spend a larger share of their income on energy than high-income households. Existing relief measures, such as the basic income scheme, the housing benefit, and subsidy programs, only partially reach these groups. A climate dividend that is automatically paid out to all residents largely mitigates excessive effects of the carbon pricing burden. However, additional aid and subsidy programs are required due to the remaining burdens on vulnerable low-income households with high energy consumption. These programs could be financed if above-average and high-income earners did not receive the climate dividend. Carbon pricing does not affect these groups as much and they generally have more opportunities to reduce their fossil energy consumption. Thus, the climate dividend should be paid to all households, but reduced unbureaucratically as a part of wage and income taxes for above-average and high-income earners.
Keywords: Q41; D31; H23; 330; carbon pricing; climate dividend; redistribution